Home Foods-Food for Thought - Lakshmi Priya, P. (Indian Journal of Marketing, 2009)
Everything in the room conveyed fumes, sweat and mopping brows. Yet toiling away tenaciously on the floor was a frail woman with her pallu wrapped demurely on her head and the end clutched in her mouth like a life saving anchor. Adding to this visage were huge gunny bags filled to the brim with jowar grains adorning to the perimeter of the room like artifacts in a museum. It all seemed like some every day scene of an obedient house wife fulfilling her core responsibility of ’Cooking for the family.’ More than that, the scene conveyed a sense of positive exuberance just like the woman herself. Meet Alka in Ameerpet, an average, uneducated homemaker who used to cringe subserviently at the very sight of her in laws or husband. But right now, it is her nervous strength and the advantage of making Jowar rotis from her child hood that is paying rich dividends for the family. Making about 100-150 rotis a day is a cakewalk for her. A delivery boy collects them and transports them to the various hostels, curry points and eateries in the vicinity of Ameerpet and SR Nagar in Hyderabad. She averages a profit of Rs.4/- per roti and her monthly income of Rs.12000/- to Rs.15000/- would clearly give an MBA fresher a serious complex. Even as the age old debate about the role of women in modern society continues, she has quietly donned a new avtaar to augment the household income.